2021
DOI: 10.1097/sla.0000000000004565
|View full text |Cite
|
Sign up to set email alerts
|

Conflicts of Interest in Studies Related to Mesh Use in Ventral Hernia Repair and Abdominal Wall Reconstruction

Abstract: Objective: To examine the accuracy of the reporting of conflicts of interest (COI) among studies related to mesh use in ventral hernia repair and abdominal wall reconstruction. Summary Background Data: Accurate declaration of COI is integral to ensuring transparency of study results. Multiple studies have demonstrated undeclared COI are prevalent in surgical literature. Methods: Studies with at least 1 American author accepted between 2014 and 2018 in 12 major, peer-reviewed general surgery and plastic sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 18 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Some journals allow corresponding authors to submit the COI forms on behalf of all authors, whereas some journals require each co-author to report their COI independently. Sekigami et al 25 suggested that authors check the OPD before they report their COI to verify the accuracy. United States–based journals may include adding a step to the journal submission process by providing a link that directs to the OPD so that the corresponding author can report COI accurately.…”
Section: Discussionmentioning
confidence: 99%
“…Some journals allow corresponding authors to submit the COI forms on behalf of all authors, whereas some journals require each co-author to report their COI independently. Sekigami et al 25 suggested that authors check the OPD before they report their COI to verify the accuracy. United States–based journals may include adding a step to the journal submission process by providing a link that directs to the OPD so that the corresponding author can report COI accurately.…”
Section: Discussionmentioning
confidence: 99%
“…Univariate analyses were used to determine the presence of study characteristics that aligned with discrepancy between declared and undeclared COI. Guided by previous research on COI of authors studying hernia mesh [ 20 ] we included impact factor (continuous), follow-up time (continuous), author’s role (e.g. first author, contributing author, senior author – categorical), and recommendations of mesh safety and effectiveness (categorical – yes/no).…”
Section: Methodsmentioning
confidence: 99%
“…First, despite many accounts of the value of mesh for hernia repair, none has reported on women, specifically, or considered that women’s greater immune response to foreign materials might predispose to disproportionate harm from insertion of the product [ 12 , 19 ]. Second, Sekigami and colleagues [ 20 ] determined that the majority of studies of mesh used for hernia repairs did not accurately report COI.…”
Section: Introductionmentioning
confidence: 99%
“…
have been explored [4][5][6], a knowledge gap persists regarding whether industry relationships have affected the broader hernia research agenda with respect to the types of research questions that are studied or the assumptions on which most studies are based. It is possible to investigate the effect of certain publications on the future scientific evaluation of key terms utilized in these sponsored publications by utilizing bibliometric analysis.
…”
mentioning
confidence: 99%